Selection of Lactiplantibacillus plantarum strains as inoculant of rice straw fermentation and its fermentation characteristics - Mernawati, Mernawati; Meryandini, Anja; Widyastuti, Yantyati (Livestock and Animal Research, 2023)
Objective: This study aimed to select Lactiplantibacillus plantarum strains suitable for inoculant of rice straw fermentation and to evaluate its fermentation characteristics.Methods: The experiment was conducted at the Feed Bioprocess Laboratory, Research Center for Applied Zoology, National Research and Innovation Agency (BRIN). This experiment was designed using a 3×4 factorial arrangement in a completely randomized design (CRD). The first factor was inoculant (1%), and the second was incubation time (7, 14, 28, and 58 days). The first stage was selection of 9 strains of L.  plantarum, based on the ability to lowering the pH and produce lactic acid. The second stage was observing the growth curve of the selected strains of L. plantarum as inoculant for rice straw fermentation. The third stage was monitoring of the rice straw fermentation characteristics, including pH values, concentration of lactic acid, water-soluble carbohydrates (WSC) and NH3-N, also dry matter, ash and crude protein. Data were analyzed based on analysis of variance, and if there was a significant effect, the data were further analyzed with Duncan’s Multiple Range Test.Results: The selected strains L. plantarum Ca098 and L. plantarum 1A-2 showed significant interaction result (p<0.05) compared with treating inoculant and ensiling days. The fermentation time influenced (p<0.05) the quality of rice straw fermentation including pH, concentration of lactic acid, WSC, NH3-N, and crude protein.Conclusions: L. plantarum Ca098 showed the best rice straw fermentation characteristics, with fleigh value of 163.86±5.97 at 58 days of fermentation. L. plantarum Ca098 showed the highest lactic acid, the lowest pH and improve crude protein content.